Сучасна українська етномузикологія в міжнародній презентації (за матеріалами 39-ї конференції Всесвітньої організації етномузикологів (ІСТМ), Відень, 2007) - Мурзіна, О. (Народна творчість та етнографія, 2009)
The article gives the Ukrainian reader an idea of the activity of world known Iternational Council for Traditional Music ( ICTM) founded in 1947. For the first time in 2009 an Ukrainian delegation took part in world Conference ICTM, held in London. A short resume of reports is proposed.